The use of cohesive ties and its relationship to critical thinking in threaded discussions / Tan Cheng Lee - Tan, Cheng Lee (2014)
This study investigated students’ use of cohesive devices in online learning environment, i.e. threaded discussion and how it reflects the critical thinking. The study aims to: 1) determine the frequency of each type of cohesive devices, i.e. reference, substitution, ellipsis and conjunctions used by participants in threaded discussion, 2) determine the students’ critical thinking abilities by using the content analysis tool established by Newman et .at in 1995, and to 3) delve into the relationship, if any, the use of the cohesive devices in reflecting the critical thinking performance of participants. The lack of the studies which focused on the language use and how it might reflect the critical thinking of its user motivated the researcher to undertake this study. Participants of the threaded discussion were the postgraduate students of the Faculty of Languages and Linguistics of a public university located in Klang Valley. A mixed method data analysis method was adopted for this study. Data was collected from the postgraduate courses’ threaded discussion assignment mediated via a learning management system named Moodles. Overall, four threaded discussion transcripts were collected and used as the source of data of this study. Halliday and Hasan (1976) Taxonomy of Grammatical Cohesion and the Newman et. al (1995) content analysis scheme were adopted to analyse the data and these two models provided quantitative results. In order to investigate the link between the use of cohesive devices and critical thinking performance, an inductive qualitative data analysis approach was used to study the context where the pronoun 'I', substitution, ellipsis and conjunction appeared and how the use of them might reflect the critical thinking performance of the participants. Based on the Halliday and Hasan (1976) Taxonomy of Grammatical Cohesion, it was found that reference is the most frequently used cohesive device, followed by the conjunction, substitution and ellipsis. In addition, after coding the data using The Newman et. al (1995) content analysis scheme, it was found that the participants’ postings mainly reflected their critical thinking ability in terms of being able to include relevant(R+ positive critical thinking indicator), clear (AC+ positive critical thinking indicator), novel (N+ positive critical thinking indicator) and justified (JS+ positive critical thinking indicator) input into the threaded discussion. It was found that in the postings, the participants integrated a lot of their personal experience into the discussion and were able to link their ideas coherently. However, it was found that the participants generally lacked the ability to critically evaluate their peers’ or their own postings. Simultaneously , the findings revealed that in terms of the use of reference, personal pronoun ‘I’ scored the highest frequency of use and it was more for conveying a personal, substantiated agreement, disagreement or viewpoint, and they would be likely to be awarded positive critical thinking indicators such as R+, AC+, C+, and N+ indicators. While in instances where pronoun 'I' had been used to convey a personal but unsubstantiated agreement, disagreement or viewpoint, they would be likely to be awarded negative critical thinking indicators such as I-, L-, C-, N- and W- indicators. As far as the use of substitution and ellipsis is concerned, it seems that the correct use of these two cohesive devices helped make the instances clear and relevant to the overall context of discussion. However, the assignment of other codes or indicators, other than clear (AC+) and relevant (R+) indicators, seems not to be influenced by the correct use of substitution and ellipsis, rather it relied on the content tried to be conveyed by the instances where substitution and ellipsis had been found. With regard to how the use of the conjunction could reflect critical thinking, the use of the adversative conjunction ‘but’ and ‘however’ appeared were found to be more frequently assigned with the positive critical thinking indicator C+ (Critical assessment of others’ or own contributions) as compared to instances of the other conjunctions. The positive critical thinking indicator JS+ (Justification) was assigned most frequently to the instances where the causal conjunction ‘because’ was found. Apart from the positive critical thinking indicators C+ and JS+, it seems that the assignment of the rest of the positive critical thinking indicators and negative critical thinking indicators was not influenced by the use of different conjunction. Instead, the assignment of the other positive and negative critical thinking indicators was dependent on content of the sentences where conjunction items were found.